The role of president director’s characteristics in affecting the corporate cash holdings on manufacturing companies listed on indonesia stock exchange - Fingga Del Asera Cona; Wirasmi Wardhani (FORUM EKONOMI, 2023)
The purpose of this study is to determine the effect of president director’s Education Major, Education Level, Age, and Tenure towards Cash Holdings on manufacturing companies. The type of data used is quantitative. The data taken is secondary data, in the form of annual report of manufacturing companies for five years, from 2015 to 2019. The sampling method used was a purposive sampling technique, thus resulting in a total sample of 130 companies. This study used the documentation method obtained from the annual and financial reports published on the official website of the Indonesia Stock Exchange. The analytical tools used are descriptive statistics and panel data regression. The result of this study indicates that (1) Education Major which proxied by MBA has a positive and significant effect on Cash Holdings. (2) Education Level has a negative and significant effect on Cash Holdings. (3) Age has a positive and insignificant effect on Cash Holdings. (4) Tenure has a positive and insignificant effect on Cash Holdings.